Radial forearm free flap variation: A case report - Janine Quek; Badrinarayanan Srinivasan; Mark Ansell; Craig J. Wales (Elsevier, 2022)
Oral cavity malignancies comprise 6-8% of all malignancies. Tumour resection and reconstruction of the defect offers the best surgical outcome. Advances in microvascular surgery has allowed increased use of free flaps as part of surgical reconstruction. This case report illustrates a rare anatomical variation of the radial forearm free flap pedicle which has been reported four times in the literature, and how we adapted our surgical management to achieve a desirable outcome.